Implementasi Kebijakan Penanganan Anak Jalanan, Gelandangan dan Pengemis di Kota Serang - Shifwa Yusriyarli; Shifa Muhaerina; Fatuahur Rohmah; Syafanissa Malika Sahiro; Dea Prastiwi Maharani; Dinda Nazwa Aulia (Jurnal Silatene Sosial Humaniora, 2026)
The implementation of handling homeless people, and beggars is a form of the government's efforts to control the community on the streets. This study aims to analyze the implementation of policies for handling street children, homeless people, and beggars in Serang City based on Regional Regulation Number 2 of 2010 and Mayor Regulation Number 41 of 2017 through the Serang City Social Service as well as support and assistance from other agencies such as the Serang City Government, Satpol PP, Health Office, Education Office, Disnaker, Dukcapil, and Serang City Police.  The research method used was qualitative descriptive with data collection through interviews, observations, and documentation at the Serang City Social Service and related communities. Based on the results of the research conducted, the factors that cause the emergence of street children are diverse, ranging from economic, psychological, educational, socio-cultural, and even religious. The handling of street children, homeless people and beggars in Serang City has not been optimal. The supporting factor of this policy is adequate human resources to discipline street children and collect them for data collection and coaching. Inhibiting factors such as lack of awareness of parents and street children are less interested in participating in the training provided by the Serang City Social Service. Therefore, it is necessary to optimize strict supervision, increase support for facilities and infrastructure, and educate the public regarding the problems of street children, homeless people, and beggars in Serang City.